2017
DOI: 10.1016/j.ebiom.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Psychiatry: Where to Next?

Abstract: The nascent field of ‘Nutritional Psychiatry’ offers much promise for addressing the large disease burden associated with mental disorders. A consistent evidence base from the observational literature confirms that the quality of individuals' diets is related to their risk for common mental disorders, such as depression. This is the case across countries and age groups. Moreover, new intervention studies implementing dietary changes suggest promise for the prevention and treatment of depression. Concurrently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
164
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(175 citation statements)
references
References 86 publications
(101 reference statements)
2
164
0
9
Order By: Relevance
“…There is a growing body of evidence to support the link between a healthy diet and better mental health outcomes [15,49]. Much of the evidence comes from cross-sectional studies, and some studies have found no association when controlling for potential confounding factors [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a growing body of evidence to support the link between a healthy diet and better mental health outcomes [15,49]. Much of the evidence comes from cross-sectional studies, and some studies have found no association when controlling for potential confounding factors [15].…”
Section: Discussionmentioning
confidence: 99%
“…AUDIT and DUDIT are screening tools to identify and grade alcohol and drug abuse or risk of. The cut points for the AUDIT include abstinence/low risk (0-7), moderate risk (8)(9)(10)(11)(12)(13)(14)(15), harmful/hazardous use (16)(17)(18)(19), or dependence . The cut points for the DUDIT are sex specific and include no drug related problems (males 0-5, females 0-1), drug related problems (males 6-24, females 2-24), or heavily dependent on drugs (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Health Behavioursmentioning
confidence: 99%
See 2 more Smart Citations
“…It remains to be tested whether these lifestyle hallmarks may be linked to western type diet. This diet is notoriously associated with high-fat and high-sugar foods consumption (55).…”
Section: Gut-microbiota-brain Axis In Regulation Of Brain Computationsmentioning
confidence: 99%